Vemurafenib (BRAF Inhibitor) Therapy for Orbital Erdheim-Chester Disease. Issue 6 (November 2017) - Gupta, Adit; Yeganeh, Amir; Rootman, Daniel; Goldberg, Robert
Abstract : Erdheim-Chester disease is a rare xanthogranulomatous systemic disease, which involves the orbit in some cases. Through this case report, the authors review the treatment modalities used in orbital Erdheim-Chester disease and explore a newer modality of treatment. Cases of orbital Erdheim-Chester disease were identified in the literature utilizing a PubMed search and all the treatment modalities were reviewed. The response to treatment of orbital Erdheim-Chester disease has been poor with the various medical and surgical treatment modalities used in the past. The authors report the use of BRAF inhibitor with a remarkable response in our case. Abstract : Erdheim-Chester disease is a rare multisystemic disorder involving the orbits. Recently, the discovery of BRAF gene mutations has added a newer dimension to the treatment of this challenging disease. The authors report the dramatic response to a BRAF inhibitor in the treatment of orbital Erdheim-Chester disease.